2018
DOI: 10.1021/acs.bioconjchem.8b00632
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Assessment of 89Zr-atezolizumab Identifies a Requirement for Carrier Added Formulations Not Observed with 89Zr-C4

Abstract: The swell of experimental imaging technologies to noninvasively measure immune checkpoint protein expression presents the opportunity for rigorous comparative studies toward identifying a gold standard. Zr-atezolizumab is currently in man, and early data show tumor targeting but also abundant uptake in several normal tissues. Therefore, we conducted a reverse translational study both to understand if tumor to normal tissue ratios forZr-atezolizumab could be improved and to make direct comparisons to Zr-C4, a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 17 publications
6
32
1
Order By: Relevance
“…In addition, choosing a dose that saturates the antigen sink in lymphoid tissue completely might tip the balance in another individual and potentially block tumour target. Indeed, it has been suggested that low specific activity 89 Zr-DFO-6E11 may be needed to accurately determine tumour PD-L1 expression levels [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, choosing a dose that saturates the antigen sink in lymphoid tissue completely might tip the balance in another individual and potentially block tumour target. Indeed, it has been suggested that low specific activity 89 Zr-DFO-6E11 may be needed to accurately determine tumour PD-L1 expression levels [21].…”
Section: Discussionmentioning
confidence: 99%
“…A 89 Zr-labeled mAb against mouse PD-L1 was used to show increased tracer uptake in a syngeneic head and neck tumor model after fractionated radiotherapy (Kikuchi et al 2017). Other research teams have also successfully employed mAbs for imaging of PD-L1 using different radionuclides, including 89 Zr, 111 In, 64 Cu and 131 I (Hettich et al 2016;Chatterjee et al 2016;Josefsson et al 2016;Nedrow et al 2017aNedrow et al , 2017bLesniak et al 2016;Li et al 2018;Moroz et al 2018;Truillet et al 2018;Pang et al 2018).…”
Section: Pd-l1 Imagingmentioning
confidence: 99%
“…A diverse selection of mouse (mPD-L1) [126,127,137] or human PD-L1 reactive (hPD-L1) [122,123,128,129,136,[138][139][140][141][142] mAbs have been investigated for their potential to detect PD-L1 levels in vivo. Most of those studies were conducted in immune compromised mice with human tumor xenografts, or in immunocompetent mice with syngeneic tumors.…”
Section: Monoclonal Antibodies and Small Proteinsmentioning
confidence: 99%